Exploring Greek UNESCO Global Geoparks: A Systematic Review of Grey Literature on Greek Universities and Future Research Avenues for Sustainable Development - Koupatsiaris, Alexandros Aristotelis; Hara Drinia (Geosciences, 2023)
The relationship between humans and the environment in the modern world is challenging. UNESCO Global Geoparks are current holistic approaches for protecting and managing geographical areas that emphasise local communities and sustainability. This paper attempts to review the grey literature of Greek universities through their academic repositories, regarding the research field referred to as Greek UNESCO Global Geoparks from 2000 to 2022 and using the keyword “Geopark” to determine possible future research directions. Through the systematic literature review methodology, from 138 bibliographic sources, 28 were selected, which met the predefined criteria. In general, there is a growing scientific–academic interest in Geoparks, which mainly concerns the aspects of geotourism (n = 7), geology (n = 6), management (n = 4), and education (n = 4). Future research directions may focus on promoting the socio-economic and cultural aspects of Geoparks, investing in collaborative management and governance of Geoparks, facing climate change and environmental challenges in Geoparks, and enhancing Geoenvironmental Education in Geoparks. Such approaches may serve the United Nation’s Seventeen Sustainable Development Goals and cultivate cognitive and emotional bonds between local populations and the geoenvironment.